Development and Characterization of Bioplastic Synthesized from Ginger and Green Tea for Packaging Applications - Md. Arefin, Kowser; Sikder Muhammad, Khalid Hossain; Md. Ruhul, Amin; Mohammad Asaduzzaman, Chowdhury; Nayem, Hossain; Osama, Madkhali; Md. Rezaur, Rahman; Muhammad Tariq, Saeed Chani; Abdullah, M. Asiri; Jamal, Uddin; Mohammed, M. Rahman (MDPI, 2023)
The world is suffering from heavy pollution because of synthetic petrochemical plastic used in our daily activities. A possible solution is the use of bioplastic synthesized from natural renewable resources. The present work investigates the development and characterization of polymer bioplastic using ginger tea and green tea to decrease the adverse effect of petrochemical plastic waste for versatile applications. Two kinds of bioplastic samples were produced with two types of tea, ginger tea and green tea, using glycerol, vinegar, starch, and water. SEM (scanning electron microscopy), FTIR (Fourier transformed infrared spectroscopy), mechanical (tensile), TGA (thermogravimetric analysis), DSC (differential scanning calorimetry), and time tests of bioplastic degradation analysis were carried out to evaluate the morphological, mechanical, and thermal behaviors of the synthesized tea bioplastics. The research result showed ginger tea bioplastic had a maximum tensile strength of 2.9 MPa and a minimum elongation of 7.46 mm. More than 78% of degradation occurred in ginger bioplastic within 30 days. Compatible thermal and morphological characteristics are also observed in the prepared bioplastic samples.